Turnover rates of roots vary considerably across temperate forage species. (December 2019) - Kagiya, Nami; Reinsch, Thorsten; Taube, Friedhelm; Salminen, Juha-Pekka; Kluß, Christof; Hasler, Mario; Malisch, Carsten S.
Abstract: Plant specialized metabolites (PSMs) have been found to reduce the activity of soil microorganisms lowering the decay rates of plant residues, which might positively affect C sequestration. Several PSM are produced by temperature forage species, but the impact of those material on decomposition has primarily been studies in forest ecosystems. Thus, the objective of this study was to i) quantify the relevant PSMs contained in the aboveground and belowground parts of forage species, ii) identify differences in CO2 -emissions resulting from the root turnover of those species, and iii) identify the main chemical root properties that affect the CO2 -emissions resulting from the root turnover. Eight cultivars of five forage species were grown in pots in a greenhouse. Aboveground- and belowground biomass was harvested and proanthocyanidins (PAs) and other PSMs (alkaloids and flavonoids) were measured. Afterwards, the roots were incubated for 58 days to investigate the root turnover while the CO2 -emissions by the decay of roots from the soil were measured. Results showed i) PA concentrations varied widely among the species (7.8–45.6 mg PA g −1 dry matter (DM)), as well as between above- and belowground biomass; ii) that CO2 -emissions differed significantly in terms of dynamics and the amount (15–40% of added C); and iii) that none of the measured root chemical properties could sufficiently explain the variance in CO2 -emissions. Nevertheless, the almost three-fold range in turnover rates shows great potential for the future in terms of specifically designing temperate grasslands via species selection to enhance potential carbon sequestration. Graphical abstract: Image 1 Highlights: Forage species differed in their metabolite profile both above- and belowground. Variability in PA concentrations existed not only among, but also within forage species. Soil respiration from plant residues varied considerably among forage species. No measured metabolite in roots adequately explained the different turnover rates.